Efektivitas Posisi Prone Dibandingkan Posisi Supine terhadap Fungsi Fisiologis Bayi Prematur - Marleny Susanthy; Yeni Rustina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine the differences in the effectiveness of the prone position compared to the supine position on the physiological functions of premature infants. The method used is the literature review. The search for articles was adjusted to the research question formulation with the PICO formula using sources from the Clinicalkey, Proquest and EBSCO databases. The results showed that the prone position intervention increased oxygen saturation, decreased heart rate and respiratory rate, reduced bradycardia and desaturation frequency, improved sleep quality and reduced stress caused by environmental factors. In conclusion, the prone position intervention proved to be more effective on the physiological function of premature infants than supine. Keywords: Premature Baby, Physiological Function, Prone Position, Supine Position, Oxygen Saturation